FUNGAL DISEASES OF SUNFLOWER AND MEASURES AGAINST THEM - Sodikov Bakhrom Sattarovich , Rakhmonov Ubaydullo Normamadovich , Khamiraev Urol Kakhramonovich , Akbarov Mirzhamol Mirodilovich (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
No special research on sunflower mycobiota has been conducted in Uzbekistan. According to regional mycological and phytopathological sources, there is very little information on sunflower diseases in Uzbekistan, so it is important to identify diseases caused by fungi in sunflower, study the cultural, morphological and biological characteristics of pathogenic species, develop measures to combat them. This article presents the results of our research on the main fungal diseases of sunflower in 2016-2019 in the fields of farms in Tashkent region in Uzbekistan, which provides information on the symptoms of the main fungal diseases of sunflower, the spread and development of the disease and the biological effectiveness of chemicals. given. The results of the study: common and multifaceted fungal diseases of sunflower were identified and measures were developed to control them, including Shavit F 72% s.e.g. against gray rot. fungicides were applied in two different doses of 2.0 kg / ha and 2.5 kg / ha. Shavit F 72% s.e.g. The highest result was obtained in the variant treated with fungicide at the rate of 2.5 kg / ha, with a biological effect of 89.5% on the leaves, 89.5% on the stem and 89.2% on the baskets, and this method was also recommended for practice;